Efeitos de diferentes intensidades de um treinamento muscular inspiratório em ciclistas recreacionais: uma abordagem metabolômica - Sakaguchi, Camila Akemi (Universidade Federal de São Carlos, 2020)
The inspiratory muscle training is a potential complementary method to sports training aiming to improve sports performance, but the metabolic mechanisms related to this technique and the best training intensity remains unknown. The analysis of the studies investigating the exercise-induced effects on human metabolome and its most relevant findings would contribute to a synthesis of the main metabolites changed by physical exercise and exercise modalities, supporting the interpretation and results in the investigation of effects to the IMT at different intensities using a metabolomics approach. Therefore, this thesis comprises 2 studies: Study 1: Aim: To provide a qualitative appraisal of metabolomics-based studies published over the past decade exploring exercise-induced alterations of the human metabolome. Methods: This review was performed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The search was performed in the following electronic databases: PubMed, Science Direct, SCOPUS and Web of Science. The quality of the studies was assessed using a scoring system created specifically for metabolomics studies. Eligibility criteria for inclusion comprised: the use of metabolomics to measure exercise-induced changes in metabolites, healthy participants, the use of serum, plasma, urine or saliva samples. Reviews, case reports, guidelines, theses and dissertations, conference abstracts, and studies using animal or in vitro models were not included. Results: from a total of 1355 studies identified, 24 were included. Of these papers, 63% focused on acute metabolite changes following intense and prolonged exercise. The best studies utilized liquid chromatography mass spectrometry (LC-MS/MS) analytical platforms with large chemical standard libraries and strong, multivariate bioinformatics support. These studies reported large-fold changes in diverse lipid-related metabolites. Metabolite shifts, even after strenuous exercise, typically return to near pre-exercise levels after one day of recovery. Conclusion: Only few studies investigated metabolite changes following acute exercise bouts of shorter durations (< 60 min) and workload volumes. Plasma metabolite shifts in these types of studies are modest comparing to high intensity and long duration exercise studies. More studies are needed to improve scientific understanding of the human system’s response to varying, chronic exercise workloads. The findings derived from this review provide direction for future investigations focused on the body’s metabolome response to exercise. Study 2: Aim: To investigate the chronic effects of different intensities of an inspiratory muscle training (IMT) on the human serum metabolome in healthy male recreational cyclists. Methods: Using a randomized, parallel group design, twenty-eight participants were randomized to three IMT groups: low intensity (LI, n=7); moderate intensity (MI, n=10), and high intensity (HI, N =11). The IMT was performed for 11 weeks. Another group of participants under the same conditions, who did not perform the IMT but participated in all procedures, was included as controls (CG, N=6). Blood samples were analyzed for metabolite shifts using 1H NMR. Statistical analysis included a 4 (group) x 2 (time) repeated measures ANOVA using the general linear model (GLM), and multivariate Principal Component Analysis (PCA). Results: Untargeted metabolomics analysis of serum samples identified 22 metabolites, including amino acids, lipids, and tricarboxylic acid cycle intermediates. Metabolites shifts did not differ between groups indicating that IMT at three intensity levels did not alter the serum metabolome relative to the control group. Conclusion: These results reveal novel insights to the metabolic effects of the IMT in human metabolomic and are consistent with the results from other studies showing negligible chronic alterations in the serum metabolome in response to physical training. Studies using more sensitive metabolomics platforms or supervised multivariate statistical analysis, large groups, and different population may continue to contribute to the investigation of the IMT metabolic effects.
Effects of different intensities of an inspiratory muscle training on recreational cyclists: a metabolomics approach
Keywords: Metabolômica; Metabolismo; Exercícios respiratórios; Força muscular; Resistência muscular; Músculo inspiratório; Metabolomics; Metabolism; Respiratory exercises; Muscle strenght; Muscle endurance; Inspiratory muscle; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL